Résurgence du mouvement antiprohibitionniste - Bertrand, Marie-Andrée (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1989)
Recently, one could witness a resurgence of the debate on the drug policy, a debate that many thought passé since the late seventies. Adding to the already existing arguments against the international conventions and the national drug laws the negative experience of 15 years of repression and the fait accompli of the lost «war against drugs», the new movement, an international one, has become openly anti-prohibitionist.